2017
DOI: 10.3390/molecules22020325
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Total Biflavonoids Extract from Selaginella doederleinii by HPLC-QTOF-MS and Its In Vitro and In Vivo Anticancer Effects

Abstract: Selaginella doederleinii Hieron has been traditionally used as a folk antitumor herbal medicine in China. In this paper, the phytochemical components of the total biflavonoids extract from S. doederleinii were studied by using high-performance liquid chromatography coupled with electrospray ionization quadrupole time-of-flight mass spectrometry (HPLC-ESI-QTOF MS/MS) in negative ion mode, and their in vitro and in vivo anticancer effects were evaluated. Four types of biflavonoids from S. doederleinii, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 27 publications
(51 reference statements)
2
45
0
2
Order By: Relevance
“…Dalam review ini, belum ditemukan studi aktivitas antioksidan secara in vivo sehingga perlu dilakukan studi aktivitas antioksidan secara in vivo untuk melengkapi database efek farmakologi dari Selaginella doederleinii Hieron. Sembilan senyawa biflavone (amentoflavone, robustaflavone, 4′-methoxy robustaflavone, podocarpusflavone, hinokiflavone, ginkgetin, dan heveaflavone) menunjukkan aktivitas antioksidan yang baik menggunakan metode DPPH (Yao et al 2017). Ekstrak etil asetat dari Selaginella doederleinii Hieron juga berpotensi sebagai sumber bioaktif alami yang mudah didapat dari alam.…”
Section: Antioksidanunclassified
“…Dalam review ini, belum ditemukan studi aktivitas antioksidan secara in vivo sehingga perlu dilakukan studi aktivitas antioksidan secara in vivo untuk melengkapi database efek farmakologi dari Selaginella doederleinii Hieron. Sembilan senyawa biflavone (amentoflavone, robustaflavone, 4′-methoxy robustaflavone, podocarpusflavone, hinokiflavone, ginkgetin, dan heveaflavone) menunjukkan aktivitas antioksidan yang baik menggunakan metode DPPH (Yao et al 2017). Ekstrak etil asetat dari Selaginella doederleinii Hieron juga berpotensi sebagai sumber bioaktif alami yang mudah didapat dari alam.…”
Section: Antioksidanunclassified
“…a, molecular formula C30H18O10) with high stability is extracted from Selaginella tamariscina , Juniperus phoenicea , Rhus succedanea , and several other plants and is commonly used in oriental medicines . Hinokiflavone is a biflavonoid active constituent of flavonoids, a class of plant secondary metabolites, which have been reported to have multiple biological properties, including antioxidative, anti‐inflammatory, antimicrobial, and antitumor . Theodoratou et al .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Hinokiflavone is a biflavonoid active constituent of flavonoids, a class of plant secondary metabolites, which have been reported to have multiple biological properties, including antioxidative, anti-inflammatory, antimicrobial, and antitumor. 12,[14][15][16][17] Theodoratou et al found strong and linear inverse associations between flavonoids and CRC risk by using data from a national prospective case-control study in Scotland. 18 Kang et al found that ochnaflavone, a natural biflavonoid, could induce cell cycle arrest and apoptosis in colon cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanolic extracts of S. involvens, S. intermedia, S. inaequalifolia, and S. tenera have been reported to possess antioxidants activity (Sivaraman et al 2013). Yao et al (2017) reported that S. doederleinii contains eight biflavonoid types which enhanced the antitumor immune response in the mouse lung cancer model. Syaefudin et al (2016) reported that nanoparticle of S. doederleinii leaves extract could inhibit A549 cancer cell growth.…”
Section: Introductionmentioning
confidence: 99%